WORK MOTIVATION FROM THE PERSPECTIVE OF HADITH - Ayub, Satry; Ahmad, La Ode Ismail; Sakka, Abdurahman (PT. Hafasy Dwi Nawasena, 2026)
Work motivation is a crucial aspect in the professional world; it is not solely viewed from a material perspective but also from a spiritual one. The primary aim of this writing is to analyze and explain how Hadith can serve as a source of work motivation for individuals, particularly for Muslims. The method employed in this research is a literature review. This analysis is conducted using a descriptive-analytical approach, where the meanings and characteristics of work motivation found in the Hadith of Prophet Muhammad (peace be upon him) are examined and studied thematically. Work motivation consists of three main components: needs, drives, and goals. There are five factors that influence work motivation from the perspective of Hadith, namely intention, a conducive environment, appreciation and recognition, understanding the importance of work, and spiritual and emotional support. In the context of work motivation, there are several Hadiths that can be referenced. One well-known Hadith is the one narrated by Al-Bukhari and Muslim regarding intention in work. The principle of work in Islam is that it is not merely an activity to earn income but also a form of worship that holds spiritual value. The principles of work in Islam, derived from the study of Hadith, encompass good intentions, honesty, hard work, and social responsibility. Through the study of Hadith, we can discover various values that can motivate individuals to work better, and by applying the values contained within these Hadiths, it is hoped that individuals can enhance their productivity and performance.